On the Iterated Exponent of Convergence of Solutions of Linear Differential Equations with Entire and Meromorphic Coefficients - Rabab Bouabdelli; Benharrat Belaïdi (Journal of Mathematics)
We investigate the zeros of the difference of the derivative of solutions of the higher-order linear differential equations f(k)+Ak-1(z)f(k-1)+⋯+A1(z)f′+A0(z)f=0 and small functions, where A0(z),…,Ak-1(z) are entire or meromorphic functions of finite iterated p order.